Comparison of Vitamin D Status Between Urban and Rural South Indian Mothers and Their Newborns - Kumar, K. Jagadish; Chavan, Abhishek; Shushma, K.; Murthy, Srinivasa (Journal of Nepal Paediatric Society, 2017)
Introduction: Though pregnant mothers are at risk of developing Vitamin D deficiency, their level differs among the urban and rural population and has various implications on newborns. This study was undertaken to compare the vitamin D status in urban and rural population of South India among pregnant women and their newborns. Material and Methods: Ninety one pregnant women and their newborns (46 urban and 45 rural) were recruited. Maternal Vitamin D levels and serum concentrations of calcium, phosphorus, alkaline phosphatase and Vitamin D were measured in the cord blood. Results: Eighty two (90%) of the pregnant women, 38 from rural and 44 from urban, had vitamin D deficiency. However, the mean vitamin D levels were low in urban (9.42 ± 12.2) compared to rural women (35.86 ± 16.3,p=0.037).Hypovitaminosis D was noted in 88% of the newborns, deficiency being more in neonates born to urban women. Though the dietary calcium intake was uniformly low, it was lower in rural (960.1 ± 139.9 mg/d) Vs urban mothers (1060.1 ± 150.6 mg/d, p< 0.001). Urban mothers were found to be exposed to sun for lower duration of 0.3 hours compared to rural mothers 0.5 hours. Similarly the surface area of body exposed to sun was lower in urban mothers (7.5%) compared to rural mothers (15%, p=0.0001). A moderate positive correlation between mother-neonate pair was noted. Conclusions: The magnitude of Hypovitaminosis D observed among pregnant women and their newborn warrants public health intervention in terms of vitamin D supplementations during pregnancy. J Nepal Paediatr Soc 2016;36(3):243-249